LONELINESS OF WORKING AND UNWORKING MALE AND FEMALE ELDER - Danis Dwi Lestari; M. Fakhrurrozi M. Fakhrurrozi (Jurnal Psikologi, 2008)
The aim of this study is to now the loneliness of the male and female elder who work and doesn’t work and also factors influencing the loneliness. The participants of this study is above 60 years old. The result shows that loneliness comes when the participants are left by his/her spouse, the grandchildren or when the spouse is already dead. The loneliness comes at the Sunday when the other family member is leaving the house. The result also shows that loneliness has relation to job or things that the participants do. Key words: loneliness, male and female elder, work and doesn’t work